The Implementation of Merdeka Belajar Curriculum: Teachers Perception - Bahri, Ulfa Lifia; Daulay, Sholihatul Hamidah (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
The reason for this consideration is to find out and get information about the issue and conceivable course of action utilization of the Merdeka Belajar Curriculum in Pematang Siantar Junior High Schools. The methodology utilized in this study is qualitative, which depicts the state of the subject and the data obtained in the midst of discernment and questions so that it becomes important information and is viably caught on by readers. The majority of this opinion was criticized by teachers regarding a course of action, requiring books, outreach from the government, and teachers' need to understand the Merdeka Belajar Instructive modules. The conceivable course of action was for the teacher to reflect and survey and, after that, ask for advice from teachers, companions, and the deputy head of the instructive programs so that they were better orchestrated to go up against the Merdeka Belajar Curriculum. Schools must complete a package book included in the Merdeka Belajar Curriculum, and the government must increase the socialization of the Merdeka Belajar Curriculum.